PENERAPAN PERTANGGUNGJAWABAN PIDANA TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM SEBAB TINDAK PIDANA EKSPLOITASI SECARA EKONOMI DAN /ATAU SEKSUAL - Manurung, Eka Rolima; Naldo, Rony Andre Christian; Pasaribu, Muldri P.J (Neolectura, 2025)
Children are prohibited from being exploited economically and/or sexually. Every person including children in conflict with the law who violates the provisions of Article 76 I of Law No. 17 of 2016 is held criminally responsible for their actions. The legal fact is that there are still children who are economically exploited (used as prostitutes). This is also the case with the legal facts in Simalungun Regency, where one of the cases has been enforced as referred to in Decision Number: 13/Pid.Sus-Anak/2023/PN Sim dated 21 December 2023. This research discusses the application of responsibility for children in conflict with the law for committing criminal offences of economic and/or sexual exploitation. This research uses a type of holistic normative research where existing data is used as a research supplement. This research is categorised as analytical prescriptive research. The data is analysed deductively qualitatively and combines 4 approaches, namely legislation approach, concept approach, philosophy approach, and case approach. This research uses the Theory of Criminal Liability. The results of the study concluded that the application of criminal responsibility for children in conflict with the law due to criminal acts of economic and / or sexual exploitation is to apply penalties based on the provisions of Article 88 jo Article 71 D paragraph (1) of Law Number 17 Year 2016. In fact, Decision Number: 13/Pid.Sus-Anak/2023/PN Sim applies a sentence based on the provisions of Article 88 of Law Number 17 of 2016.